2018
DOI: 10.4103/jfmpc.jfmpc_261_17
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of metabolic syndrome and associated risk factors among geriatric population living in a high altitude region of rural Uttarakhand, India

Abstract: Introduction:Metabolic syndrome (MetS) is responsible for 2.5-fold increase in cardiovascular mortality and a 5-fold higher risk of developing diabetes.Materials and Methods:A community-based cross-sectional study was conducted during 2015–2016 in District Nainital. A list of all villages was developed. From this list, thirty villages were identified using population proportionate to size sampling method. From each village, thirty geriatric subjects (GSs) were selected. The study population included 979 GSs ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…This finding is consistent with studies in China, Qatar and Nepal [20][21][22] whereas, it contradicts the finding from a study in Uttarakhand, India. 23 It is evident from the current study that there is significant association between metabolic syndrome and place of residence. People of rural residence are less likely to have metabolic syndrome as compared to the urban dwellers who are at a greater risk of metabolic syndrome.…”
Section: Discussionmentioning
confidence: 55%
“…This finding is consistent with studies in China, Qatar and Nepal [20][21][22] whereas, it contradicts the finding from a study in Uttarakhand, India. 23 It is evident from the current study that there is significant association between metabolic syndrome and place of residence. People of rural residence are less likely to have metabolic syndrome as compared to the urban dwellers who are at a greater risk of metabolic syndrome.…”
Section: Discussionmentioning
confidence: 55%
“…A number of studies have been carried out across different parts of India and have shown considerable variations in the prevalence of metabolic syndrome. 27 , 28 , 29 , 30 , 31 , 32 , 33 A recent meta-analysis 34 of 111 Indian studies reported a pooled prevalence of 30% among Indian adults (≥ 18 years).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a study 40 in the national capital region of India reported urban prevalence (NCEP ATP-III) as 21.7% in male participants and 27.8% in female participants, whereas corresponding numbers for rural sites were 13.8% and 18.8%. Kapil et al 27 reported 28.6% prevalence among individuals aged 60 and above from a rural community from a high-altitude region in district of Nainital in northern India, based on the IDF criteria. On the other hand, two studies on older adults in the same age group (≥ 60 years) and using the same (IDF) criteria from an urban setting in central India revealed a much higher prevalence (42.1%).…”
Section: Discussionmentioning
confidence: 99%
“…In agreement to the results of this study, a cross-sectional study that was conducted on 211 subjects showed that the prevalence of MetS (based on the International Diabetes Federation criteria) among H. pylori +ve and H. pylori -ve patients was 76.6% versus. 69.8% (p=0.27), according to NCEP-ATPIII criteria it was 90.4% vs. 87.2% (p=0.5), and the differences was not significant [26]. In addition, Kim et al [27] showed that H. pylori seropositivity was not associated with the presence of metabolic syndrome among 37,263 subjects (according to the NCEP ATP III criteria).…”
Section: Anemia Is One Of the Complications Of H Pylori Infection The...mentioning
confidence: 93%